Feeding Prometheus: An Interdisciplinary Approach for Solving the Global Food Crisis - Vandermeer, John; Aga, Aniket; Allgeier, Jake; Badgley, Catherine; Baucom, Regina; Blesh, Jennifer; Shapiro, Lilly F.; Jones, Andrew D.; Hoey, Lesli; Jain, Meha; Perfecto, Ivette; Wilson, Mark L. (Frontiers in Sustainable Food Systems, 2018)
The current global food system is inadequate to meet the needs of the current world population without compromising future well-being. For example, current intensified production systems lead to undernutrition in some regions coupled with epidemics of obesity in others while compromising their underlying ecological foundations, such as creating areas of ocean hypoxia. Such common observations challenge the research community to ask new types of basic questions and apply novel analytical frameworks for analyzing them. Elaboration of an integrated applied research agenda is imperative to addressing these global food system challenges. We propose that core competencies of a new analytical framework lie at the intersection of four domains: (1) the ecology of agroecosystems; (2) equity in global and local food systems; (3) cultural dimensions of food and agriculture; and (4) human health. This intersection constitutes a new analytical framework for transitions toward global food system sustainability.